Exclusive breastfeeding and determinant factors of early weaning: an integrative literature review (Research, Society and Development, 2023)
This article aims to identify the prevalence of exclusive breastfeeding and the main factors that lead nursing mothers to interrupt exclusive breastfeeding before the baby is six months old. This is an integrative literature review, based on the PubMED electronic database, using the descriptors “Aleitamento Materno/Breastfeeding” and “Desmame/Weaning” with the Boolean operators “e/AND”. In the initial search, 3097 articles were found. After applying the inclusion and exclusion criterions, 15 studies were analyzed. Exclusive breastfeeding rates ranged from 14.8% to 98.1%. The main factors associated with early weaning were: low level of education of the mother, unstable marital situation, woman returning to work, maternal beliefs and myths, breast problems, in addition to emotional aspects of the puerperal woman. It is possible to observe that the prevalence of breastfeeding in Brazil is far below the recommended and expected levels, that breastfeeding is a multifactorial practice, and that early weaning is related to different factors. In view of this, it is necessary to implement pre and postnatal care, with information on breastfeeding, its practice and advantages, in addition to formulating effective strategies to improve the prevalence of breastfeeding in Brazil. It is also important to carry out regional research with more elaborate methodologies in order to highlight the causes that impact early weaning in that location, and thus formulate effective strategies to improve the prevalence of breastfeeding in Brazil.